Gillnets Selection of Alburnus chalcoides (Güldenstädt, 1772) in Almus Dam Lake (Tokat, Turkey) - Mehmet Karataş (International Journal of Aquatic Biology, 2015)
In this study gill-net selectivity for Alburnus chalcoides inhabiting the Almus Dam Lake was estimated. Experimental gill-net fishing was conducted using gill-net with 15 mm and 20 mm mesh-size, during October 2002 and September 2003. A total of 254 and 198 specimens of A. chalcoides were caught by gill-net with 15 mm and 198 with the 20 mm mesh-size, respectively. The total length of the fish ranged from 10.5 cm to 21.5 cm for 15 mm mesh-size and 13.6 cm to 25.6 cm for 20 mm mesh-size. Mean total lengths were calculated as 14.34 ± 1.52 cm and 17.85 ± 1.97 cm for 15 mm and 20 mm mesh-size, respectively. Selectivity analysis indicated an optimum length (100% probability of retention) of 14.77 cm for the 15 mm mesh size and 19.69 cm for the 20 mm mesh size gill-nets. Selectivity Factor was calculated as 0.9846. The vast majority (81%) of fish caught by 15 mm mesh size and 20 mm mesh size were mature. Therefore, both the 15 mm and 20 mm mesh size were suitable for the sustainable fisheries of A. chalcoides in the Almus Dam Lake.